Power-law Distribution of Solar Cycle–modulated Coronal Jets - Jiajia Liu; Anchuan Song; David B. Jess; Jie Zhang; Mihalis Mathioudakis; Szabolcs Soós; Francis P. Keenan; Yuming Wang; Robertus Erdélyi (The Astrophysical Journal Supplement Series, 2023)
Power-law distributions have been studied as a significant characteristic of nonlinear dissipative systems. Since discovering the power-law distribution of solar flares that was later extended to nanoflares and stellar flares, it has been widely accepted that different scales of flares share the same physical process. Here we present the newly developed semiautomated jet identification algorithm and its application for detecting more than 1200 off-limb solar jets during Solar Cycle 24. Power-law distributions have been revealed between the intensity/energy and frequency of these events, with indices found to be analogous to those for flares and coronal mass ejections (CMEs). These jets are also found to be spatially and temporally modulated by the solar cycle, forming a butterfly diagram in their latitudinal-temporal evolution, experiencing quasi-annual oscillations in their analyzed properties, and very likely gathering in certain active longitudinal belts. Our results show that coronal jets display the same nonlinear behavior as that observed in flares and CMEs, in solar and stellar atmospheres, strongly suggesting that they result from the same nonlinear statistics of scale-free processes as their counterparts in different scales of eruptive events. Although these jets, like flares and other large-scale dynamic phenomena, are found to be significantly modulated by the solar cycle, their corresponding power-law indices still remain similar.